Effects of local and systemic ketorolac application on rat femur fracture healing - Bailey V. Fearing, PhD; Katherine K. Li, MD; Sarah M. Romereim, PhD; Matthew R. Smykowski, BS; K. Eddie Afetse, BS, BA; Elaina K. Ball, BS; Susan Odum, PhD; Marc Duemmler, MS; Nahir A. Habet, MS; Rachel B. Seymour, PhD; Joseph R. Hsu, MD (OTA International)
Abstract. Objectives:. Nonsteroidal anti-inflammatory drugs (NSAIDs) are frequently administered in patients with orthopaedic trauma because of their effectiveness in pain reduction and managing inflammation, but clinicians are concerned regarding the possibility that NSAID use may increase the risk of delayed fracture healing or nonunion. Prior research is not definitive in this regard, showing variable association between bone healing and systemic NSAID administration. In addition to the inconclusive results regarding systemic NSAIDs, the effects of locally applied NSAIDs on fracture healing have not widely investigated. The purpose of this study was to examine the effects of local ketorolac in an open femur fracture rat model compared with systemic ketorolac and placebo. Methods:. After a standardized open femur fracture stabilized with an intramedullary pin, animals were divided into 3 treatment groups: (A) a negative control collagen sponge soaked in saline, (B) a collagen sponge soaked in ketorolac, and (C) systemic delivery of ketorolac by intraperitoneal injection. Micro computed tomography and mechanical testing were used to assess fracture healing 14, 42, and 84 days after surgery. Results:. Significant differences in quantifiable fracture healing were observed between the 3 euthanasia time points, with greater fracture healing over time regardless of treatment. However, there were no significant differences observed in the callus size, callus strength, degree of fracture healing, bone mineral density, or bone volume/tissue volume between treatment groups at any time point. Conclusions:. These data suggest no detrimental effect of local or systemic ketorolac on fracture healing in this small animal model of femur fracture healing.